Cerebral oxygen saturation after multiple perioperative influential factors predicts the occurrence of postoperative cognitive dysfunction. Issue 1 (December 2015) - Ni, Cheng; Xu, Ting; Li, Nan; Tian, Yang; Han, Yongzheng; Xue, Qingsheng; Li, Min; Guo, Xiangyang
Abstract Background Postoperative cognitive dysfunction (POCD) is a frequent complication in elderly patients undergoing major non-cardiac surgery, but its etiology is still unclear. Cerebral oxygen saturation (ScO2 ) represents the balance of cerebral oxygen supply and demand. The aim of present study was to evaluate the relationship between perioperative ScO2 and POCD, and to verify the hypothesis that the value of ScO2 after multiple perioperative influential factors could predict POCD in elderly patients undergoing total knee arthroplasty (TKA). Methods Seventy eight Patients aged more than 65 years undergoing elective TKA with intrathecal anesthesia were enrolled. Cognitive functions were assessed one day before and 6 days after surgery, and POCD were defined according to ISPOCD. Demographics were recorded. Perioperative ScO2, blood pressure (BP), blood gas analysis and other clinical data were monitored and recorded, then the decrease of ScO2, BP and PaO2 after influential factors were calculated. Results POCD occurred in 15 patients (19.2 %). BP decreased after anesthesia induction and tourniquet deflation, and PaO2 decreased after cement implantation was higher in POCD group. ScO2 of POCD group is significantly lower than non-POCD group (P < 0.05), and the absolute value and percentage decrease of ScO2 became significant between two groups after multiple influential factors. ScO2 after all influential factors (anesthesia induction, cement implantation and tourniquet deflation) had the best predictive performance for POCD (AUC = 0.742), and the optimal threshold was 66.5 %. Conclusions Perioperative ScO2 of patients with POCD is lower than patients without POCD. ScO2 after multiple perioperative influential factors could be an effective predictor for POCD, which reveal an important role of ScO2 decrease in the development of POCD and provide possible treatment target.